Impact of Crop Rotation, Government Support, and Financial Institute Support towards the Profitability of Organic Farming: A Study with Special Reference to Organic Vegetable Farmers in Kurunegala District – Sri Lanka - A. R. W. S. B .Ranawana; R.N. Weerasinghe (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The growing yearning for safer foods and the increased environmental responsiveness has boomed the organic products category to one of the most growing in the food sector. The aim of this research is to investigate the impact of the Crop Rotation, Government Support and the Financial Institute Support on profitability of organic vegetable production in Sri Lanka. Hence, this research addresses the practices of crop rotations, financial support and the government support given to organic farmers as determinants to enhance the profitability such farmers. A structured questionnaire was employed in this study to collect primary data and obtained 81 responses from farmers in Kurunegala district. The sample consisted of farmers who produce and market organic vegetables in Sri Lanka. SPSS 20 version is used to analyse the results derived from the farmers. According to the analysis of collected data, this research concluded that organic farming is perceived to be more profitable than conventional farming. However, still the profitability remains below the satisfactory level of farmers. Hence, they think that doing another job or business would have bought them higher financial benefits than what they got from organic farming. Results of the study confirmed that crop rotation brings more profits to organic farming. Further, it emphasized that the banking support has a significant influence on the profitability of organic farming while finding shows that the government support was not sufficiently given towards the organic farming. In this regard, study presents respondents’ feedback on how government could help in increasing profits of organic farmers.